Sentiment Analysis of Rising Fuel Prices on Social Media Twitter using the Naïve Algorithm Bayes Classifiers And AdaBoost - Hendriyadi, Imam; Putri, Angela Febrianti; Rahmawati, Rahmawati; Saputra, Dedi Dwi (Informatics and Software Engineering, 2023)
The government issued a policy of increasing the price of Indonesian fuel oil (BBM) in September 2022. This policy resulted from the war in Europe between Russia and Ukraine, which caused a surge in world oil prices because many respondents complained about the increase in fuel. This condition has caused much controversy or opinion among the public on social media, especially Twitter. With this phenomenon, sentiment analysis uses the Naïve Bayes classifiers algorithms to see how the public responds to government policies. The classification used in this sentiment analysis is Complaint or Not Complaint. Sentiment analysis of fuel rise on Twitter using Naïve Bayes classifier algorithm and AdaBoost Naïve Bayes classifier algorithm is applied to get the best classification By using hashtag tweets The increase in the price of fuel oil (BBM) which was taken 1000 tweets to be Used US a dataset. Data preprocessing consists of Text, Status, removal annotations, Remove hashtags, Remove urls, regexp, Indonesian stemming, and Indonesian stopword removal. The analysis results obtained an accuracy value of 70.69%, precision of 70.49%, recall of 71.45%, and AUC of 0.729 (good classification).   Pemerintah mengeluarkan kebijakan menaikkan harga bahan bakar minyak (BBM) Indonesia pada September 2022. Kebijakan ini adalah hasil dari perang di Eropa antara Rusia dan Ukraina hal ini menyebabkan lonjakan harga minyak dunia karena banyak responden masyarakat yang mengeluhkan atas kenaikan BBM. Hal ini banyak menimbulkan kontroversi ataupun opini pada kalangan masyarakat di social media khususnya twitter. Dengan adanya fenomena tersebut, untuk melihat bagaimana tanggapan masyarakat terhadap kebijakan pemerintah maka dilakukan analisis sentimen menggunakan algoritma naïve bayes classifier. Klasifikasi yang digunakan pada analisis sentimen ini adalah Complaint atau Not complaint. Analisis sentimen kenaikan bahan bakar pada twitter menggunakan algoritma naive bayes classifier dan adaboost, algoritma naïve bayes classifier ini diterapkan untuk mendapatkan klasifikasi terbaik. Dengan menggunakan hashtag tweets Kenaikan harga bahan bakar minyak (BBM) yang diambil 1000 tweet untuk di jadikan dataset. Preprocessing data terdiri dari Text, Status, Remove annotations, Remove hastag, Remove url, Regexp, Indonesian stemming, Indonesian stopword removal. Hasil analisis tersebut didapatkan nilai accuracy 70,69%, precision 70,49%, recall 71,45%, dan AUC yang didapat sebesar 0,729 (good classification).